Enhancement of Lipase Enzyme Activity in Non-Aqueous Media through a Rapid Three Phase Partitioning and Microwave Irradiation - N. Saifuddin; A. Z. Raziah (E-Journal of Chemistry)
Three phase partitioning is fast developing as a novel bio-separation strategy with a wide range of applications including enzyme stability and enhancement of its catalytic activity. pH tuning of enzyme is now well known for use in non-aqueous systems. Tuned enzyme was prepared using a rapid drying technique of microwave dehydration (time required around 15 minutes). Further enhancement was achieved by three phase partitioning (TPP) method. With optimal condition of ammonium sulphate and t-butanol, the protein appeared as an interfacial precipitate between upper t-butanol and lower aqueous phases. In this study we report the results on the lipase which has been subjected to pH tuning and TPP, which clearly indicate the remarkable increase in the initial rate of transesterification by 3.8 times. Microwave irradiation was found to increase the initial reaction rates by further 1.6 times, hence giving a combined increase in activity of about 5.4 times. Hence it is shown that microwave irradiation can be used in conjunction with other strategies (like pH tuning and TPP) for enhancing initial reaction rates.